(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
This study analyzes the customer relationship management (CRM) strategy of Hilton Samarkand Regency Amir Temur and evaluates its effectiveness in improving customer satisfaction, loyalty, and operational performance. The research focuses on customer segmentation, targeting, customer journey mapping, complaint management, service quality assessment, and the use of CRM technologies. A qualitative case study approach was used based on secondary data, hotel performance indicators, customer reviews, and strategic analysis tools such as SWOT and PESTEL analysis. Findings indicate that Hilton Samarkand Regency has strong international brand recognition, high service quality standards, and advanced CRM technologies such as OnQ PMS and Salesforce integration. However, challenges remain in customer retention, local customer loyalty, Wi-Fi quality, and technological complexity. The study recommends the implementation of localized loyalty programs, AI-powered customer service systems, stronger cooperation with local businesses, and improved employee training. The research concludes that effective CRM implementation significantly contributes to competitive advantage and customer satisfaction in the hospitality industry of Uzbekistan.